(untitled) (Research, Society and Development, 2025)
Introduction: The Surgical Center performs interventions with safety, requiring a qualified performance from the multidisciplinary team, especially nursing, which stands out for its close contact with patients, leadership, and conflict management. However, distractions during care may compromise patient safety. Objective: To identify, in the literature, the dilemmas faced by nurses in the Surgical Center in providing qualified care. Methods: Integrative review based on the PRISMA method. The descriptors used were: “Nursing” AND “Surgical Center” AND “Organization and Administration.” The search was conducted between July and August 2024 in the PubMed and Virtual Health Library (VHL) databases. Inclusion criteria: original articles, in any language, available electronically, with no time restriction, and that answered the research question. Results: Communication was identified as one of the main dilemmas faced by nurses, particularly in interprofessional interactions. The lack of effective communication compromises care and patient safety, being associated with the absence of open dialogue, mutual trust, and weak team management. Conclusion: The findings reinforce the importance of communication in the surgical environment. It is expected that this topic will be further explored in future studies to support the development of strategies that promote safer and more qualified nursing care.